2010
DOI: 10.1002/ptr.3174
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal eugenol administration alleviates neuropathic pain in male Sprague‐Dawley rats

Abstract: The main objective of this study was to determine the central effect of eugenol on neuropathic pain when injected intrathecally at the level of the lumbar spinal cord. In a preliminary study the penetrability of eugenol was evaluated in the CNS of rats. Blood, brain and spinal cord samples were collected at selected time points following eugenol administration and concentrations were determined by tandem liquid chromatography-mass spectrometry. Brain-to-plasma and spinal cord-to-plasma ratios (3.3 and 6.7, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…EUGL eugenolol, EUGD eugenodilol this study is about 1 μM. A recent report (Lionnet et al 2010) showed that there was a high ratio of brain-to-plasma and spinal cord-to-plasma, suggesting that EUG can penetrate the brain well. The anti-epileptic effect of EUG observed in this study may occur at a concentration achievable in humans.…”
Section: Discussionmentioning
confidence: 83%
“…EUGL eugenolol, EUGD eugenodilol this study is about 1 μM. A recent report (Lionnet et al 2010) showed that there was a high ratio of brain-to-plasma and spinal cord-to-plasma, suggesting that EUG can penetrate the brain well. The anti-epileptic effect of EUG observed in this study may occur at a concentration achievable in humans.…”
Section: Discussionmentioning
confidence: 83%
“…Ohkubo and Shibata [100] have shown that eugenol inhibits formalin-induced nociceptive responses in mice. Furthermore, eugenol alleviated neuropathic pain in sciatic nerve ligation rat models [101]. A similar alleviation was produced by the oral administration of eugenol [102].…”
Section: Actions Of Plant-derived Trp Agonists On Synaptic Transmimentioning
confidence: 87%
“…In rat models, the agent has been demonstrated to be effective in relieving pain from orofacial regions and other peripheral regions (Park et al, 2009;Lionnet et al, 2010;Yeon et al, 2011). For example, Park and his colleagues showed that subcutaneous injection of eugenol into the left vibrissa pad dose-dependently decreased the latency time of head withdrawal in response to thermal stimuli and application of eugenol onto inferior alveolar nerve reduced jaw-opening reflex in response to noxious electrical stimulation to anterial tooth pulp.…”
Section: Discussionmentioning
confidence: 99%